Peran Green Marketing dan Transparansi Rantai Pasok dalam Kepercayaan Konsumen Halal - Muhammad Affan Amin (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2026)
This study examines how green halal marketing and halal supply chain transparency shape consumer trust toward halal products in Indonesia, evaluated through a Maqasid Syariah framework. The urgency is underscored by a critical gap: despite Indonesia’s position as the world’s second-largest halal economy (SGIE, 2024/2025), only 28.8% of food and beverage enterprises had obtained mandatory halal certification as of February 2025 (BPJPH, 2025). Using a qualitative descriptive approach grounded in Systematic Literature Review (SLR) following the PRISMA protocol across Scopus and Google Scholar (2019–2026), supplemented by multi-source secondary data from BPS, BPJPH, KNEKS, Bank Indonesia, and digital marketplace platforms, this study constructs the Green-Halal-Chain Trust Model positioning green halal marketing (X1) and halal supply chain transparency (X2) as dual determinants of halal consumer trust (Y). Findings are validated through theoretical triangulation across Islamic jurisprudential, marketing, and consumer behaviour frameworks. Results confirm that both variables are deeply rooted in the principles of hifz al-din, hifz al-nafs, and hifz al-mal, contributing three original propositions to Islamic marketing literature.